Accountability and Learning: Exploding the Myth of Incompatibility between Accountability and Learning - Guijt, Irene (NGO Management, 2010)
When accountability is understood as reporting on pre-deined deliverables, it is often considered to be irreconcilable with learning. This conventional wisdom inhibits an appreciation of their connection. In this chapter, Irene Guijt exposes the laws and traps in reasoning that keep accountability and learning apart. She provides practitioners with principles and basic good ideas that open up prospects for accountability and learning to complement each other.

Developmental Evaluation: Applying Complexity Concepts to Enhance Innovation and Use - Patton, Michael Quinn (Guilford Press, 2010)
Developmental evaluation (DE) offers a powerful approach to monitoring and supporting social innovations by working in partnership with program decision makers. In this book, eminent authority Michael Quinn Patton shows how to conduct evaluations within a DE framework. Patton draws on insights about complex dynamic systems, uncertainty, nonlinearity, and emergence. He illustrates how DE can be used for a range of purposes: ongoing program development, adapting effective principles of practice to local contexts, generating innovations and taking them to scale, and facilitating rapid response in crisis situations. Students and practicing evaluators will appreciate the book's extensive case examples and stories, cartoons, clear writing style, "closer look" sidebars, and summary tables. Provided is essential guidance for making evaluations useful, practical, and credible in support of social change.See also Developmental Evaluation Exemplars, edited by Michael Quinn Patton, Kate McKegg, and Nan Wehipeihana, which presents 12 in-depth case studies.
Keywords: Evaluation; Measurement; Organizational effectiveness; Project management

Quality standards for development evaluation - OECD; Development Assistance Committee (OECD, 2010)
Based on a broad international consultative process, the DAC Quality Standards for Development Evaluation are a reference guide to good practice in development evaluation. With a view to improving the quality of evaluation processes and products, and facilitating collaboration, this reference guide lays out standards for each phase of a typical evaluation process: from defining purpose, to planning, designing, implementing, reporting, and learning from and using evaluation results.
OCLC: 631212078

Naturalizing sensemaking - Snowden, Dave (Informed by Knowledge: Expert Performance in Complex Situations, 2010)
The focus of this book is on how experts adapt to complexity, synthesize and interpret information in context, and transform or "fuse" disparate items of information into coherent knowledge. The chapters examine these processes across experts (e.g. global leaders, individuals in extreme environments, managers, police officers, pilots, commanders, doctors, inventors), across contexts (e.g. space and space analogs, corporate organizations, command and control, crisis and crowd management, air traffic control, the operating room, product development), and for both individual and team performance. Successful information integration is a key factor in the success of diverse endeavors, including team attempts to climb Mt. Everest, crowd control in the Middle East, and remote drilling operations. This volume is divided into four sections, each with a specific focus on an area of expert performance, resulting in a text that covers a wide range of useful information. These sections present well-researched discussions, such as: the management of complex situations in various fields and decision contexts; technological and training approaches to facilitate knowledge management by individual experts and expert teams; new or neglected perspectives in expert decision making; and the importance of ‘modeling’ expert performance through techniques and frameworks such as Cognitive Task Analysis, computational architectures based on the notion of causal belief mapping such as ‘Convince Me,’ or the data/frame model of sensemaking. The volume provides essential reading for researchers and practitioners of Naturalistic Decision Making and those who study Expertise; Organizational and Cognitive Psychologists; and researchers and students in Business and Engineering.